Investigating the anatomy of magnetosheath jets - MMS observations - Karlsson,T; Plaschke,F; Hietala,H; Archer,M; Blanco-Cano,X; Kajdic,P; Lindqvist,P-A; Marklund,G; Gershman,DJ (ANNALES GEOPHYSICAE, 2018)
We use Magnetosphere Multiscale (MMS) mission data to investigate a small number of magnetosheath jets, which are localized and transient increases in dynamic pressure, typically due to a combined increase in plasma velocity and density. For two approximately hour-long intervals in November, 2015 we found six jets, which are of two distinct types. (a) Two of the jets are associated with the magnetic field discontinuities at the boundary between the quasi-parallel and quasi-perpendicular magnetosheath. Straddling the boundary, the leading part of these jets contains an ion population similar to the quasi-parallel magnetosheath, while the trailing part contains ion populations similar to the quasi-perpendicular magnetosheath. Both populations are, however, cooler than the surrounding ion populations. These two jets also have clear increases in plasma density and magnetic field strength, correlated with a velocity increase. (b) Three of the jets are found embedded within the quasi-parallel magnetosheath. They contain ion populations similar to the surrounding quasi-parallel magnetosheath, but with a lower temperature. Out of these three jets, two have a simple structure. For these two jets, the increases in density and magnetic field strength are correlated with the dynamic pressure increases. The other jet has a more complicated structure, and no clear correlations between density, magnetic field strength and dynamic pressure. This jet has likely interacted with the magnetosphere, and contains ions similar to the jets inside the quasi-parallel magnetosheath, but shows signs of adiabatic heating. All jets are associated with emissions of whistler, lower hybrid, and broadband electrostatic waves, as well as approximately 10s period electromagnetic waves with a compressional component. The latter have a Poynting flux of up to 40µWm−2 and may be energetically important for the evolution of the jets, depending on the wave excitation mechanism. Only one of th